2007
DOI: 10.1021/ie0701064
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thermal-Swing Sorption-Enhanced Reaction Process Concept for Hydrogen Production by Low-Temperature Steam−Methane Reforming

Abstract: Hydrogen production by steam reforming of natural gas is a well-established technology. The possibility of using hydrogen, a nonpolluting fuel, in fuel cells has brought new interest in developing small, efficient, fuel-cell grade hydrogen production units for residential or industrial use. A novel, step-out, low-temperature, steam−methane reforming (SMR) process concept called “thermal-swing sorption-enhanced reaction” (TSSER) is described. The concept simultaneously carries out the SMR reactions at 490−590 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 21 publications
3
86
1
Order By: Relevance
“…Generally, an integral fixed-bed reactor with a mixture of the steam reforming catalyst and solid sorbent to selectively remove CO 2 is used. This process is well known as the sorption-enhanced reaction process and has been widely studied by steam methane reforming (Mayorga, et al, 1999;Ding, et al, 2000;Balasubramanian, et al, 1999;Kinoshita, et al, 2003;Yi, et al, 2005;Lee, et al, 2007;Li, et al, 2007;Essaki, et al, 2008;Harrison, 2008). For example, Balasubramanian et al (1999) reported on H 2 production through sorptionenhanced reaction process using a laboratory-scale fixed bed reactor containing a reforming catalyst and CaO formed by calcination of high-purity CaCO 3 , the results of which showed that a gas with a hydrogen content up to 95 % (dry basis) could be produced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, an integral fixed-bed reactor with a mixture of the steam reforming catalyst and solid sorbent to selectively remove CO 2 is used. This process is well known as the sorption-enhanced reaction process and has been widely studied by steam methane reforming (Mayorga, et al, 1999;Ding, et al, 2000;Balasubramanian, et al, 1999;Kinoshita, et al, 2003;Yi, et al, 2005;Lee, et al, 2007;Li, et al, 2007;Essaki, et al, 2008;Harrison, 2008). For example, Balasubramanian et al (1999) reported on H 2 production through sorptionenhanced reaction process using a laboratory-scale fixed bed reactor containing a reforming catalyst and CaO formed by calcination of high-purity CaCO 3 , the results of which showed that a gas with a hydrogen content up to 95 % (dry basis) could be produced.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also showed that CO 2 sorption enhancement enables the use of a lower reaction temperature, which may reduce energy usage and catalyst sintering. At the same time, it is possible for the steam reforming process to 5 use less expensive reactor materials (Ding, et al, 2000;Lee, et al, 2007;Essaki, et al, 2008;Harrison, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] These materials are currently being studied for CO 2 capture at the intermediate temperatures (300-500 8C) and relatively high pressures (> 25 bar) that are used in the process of hydrogen production. [7][8][9][10][11] In particular, sorptionenhanced water-gas shift (SEWGS) is a technology that is currently at the development stage that can be advantageously used in pre-combustion decarbonisation for CO 2 free electricity production. [12] It combines a high-temperature CO 2 sorbent and a high-temperature water-gas shift catalyst to produce two hot and separate H 2 and CO 2 product streams from syngas.…”
Section: Introductionmentioning
confidence: 99%
“…These results show the potential of hightemperature PSA cycle for carbon capture. As far as TSA is concerned, recently, Lee et al 80 proposed a strategy that combines SMR with TSA directly producing fuel cell grade hydrogen. A K 2 CO 3 promoted hydrotalcite was used as CO 2 chemisorbent.…”
Section: Sorption Enhanced Steam Methane Reformingmentioning
confidence: 99%